Non-invasive Respiratory Support in COVID-19: A Narrative Review - Luján, Manel; Sayas, Javier; Mediano, Olga; Egea, Carlos (Frontiers in Medicine, 2022)
Acute respiratory failure secondary to COVID 19 pneumonia may require a variety of non-pharmacological strategies in addition to oxygen therapy to avoid endotracheal intubation. The response to all these strategies, which include high nasal flow, continuous positive pressure, non-invasive ventilation or even prone positioning in awake patient can be highly variable depending on the predominant phenotypic involvement. The decision of when to substitute conventional oxygen therapy for an non-invasive respiratory support, which one to choose, the role of combined methods, the definition and attitude towards therapeutic failure or de-escalation procedures in case of improvement are clinical questions directly related to the daily care of the severe COVID 19 patient. The experience accumulated after more than a year of the pandemic should allow the elaboration of recommendations that answer to all these questions.